KKN 29. Membangun Desa Berkualitas Melalui Pengadaan Pengajian di Masjid Al-Iqram Serta Sosialisasi Pembentukan Ikatan Remaja Masjid: Modersasi Beragama - Hafizh, Agil Raga; Randi Raharja Rahmatulloh; Reilham Riziq Algani; Fenny Fatriany (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The purpose of this research is to describe one form of community service by KKN (Student Community Service) students involving various stakeholders as a means of socializing religious knowledge and efforts to enhance the Islamic potential of the village community. This research employs the Sisdamas (Community Empowerment System) methodology and adopts a qualitative approach with phenomenology. In its implementation, routine religious activities are conducted, including the recitation of blessings (shalawat) and the study of Islamic jurisprudence (fiqih). The outcome of this program is that the community in RW 09 has formed a youth mosque association and understands its organizational structure. Furthermore, regular religious gatherings are now held every Friday evening. We hope that the establishment of IRMA and the continuation of these regular religious activities can be carried out after the KKN period.